Frontal Assessment Battery in Persian population with Parkinson’s disease - Farzad Ashrafi; Mostafa Daemi; Sina Asaadi; Davood Ommi; Zahra Nasiri; Hossein Pakdaman (International Clinical Neuroscience Journal, 2014)
Background: Several studies have indicated that executive dysfunction is the main neuropsychological feature of Parkinson’s disease (PD). The Frontal Assessment Battery (FAB) is a short tool for the assessment of executive functions. Purpose: The aim of this study was to determine the relationship between Persian version of FAB scores and age, education, Mini-Mental State Examination (MMSE), and severity of the disease in Iranian patients with PD. Methods: The study involved 60 healthy participants and 60 patients with idiopathic PD. Age, sex, disease duration, and Unified Parkinson’s Disease Rating Scale (UPDRS) scores were noted. FAB and MMSE were administered to all participants. Both groups were compared according to FAB scores, MMSE, age, and education. Results: FAB scores were significantly lower in patients with PD than in healthy controls (P<0.05). In patients with PD, FAB scores were correlated with MMSE (P<0.05) but not with UPDRS (P=0.93). Conclusion: FAB scores were significantly lower in Iranian patients with PD in comparison to controls and it can indicate that this battery has good discriminate validity and can be a useful tool to identify executive dysfunction in Iranian patients with Parkinson’s disease. Also it seems that FAB is not useful test to show disease severity in Iranian patients.